Prevalence of Substance Use Among Patients of Community Health Centers in East Los Angeles and Tijuana. (23rd February 2017) - Gelberg, Lillian; Natera Rey, Guillermina; Andersen, Ronald M.; Arroyo, Miriam; Bojorquez-Chapela, Ietza; Rico, Melvin W.; Vahidi, Mani; Yacenda-Murphy, Julia; Arangua, Lisa; Serota, Martin
ABSTRACT: Background: Given the increased use of psychoactive substances on the United States–Mexico border, a binational study (Tijuana, Mexico–Los Angeles, USA) was conducted to identify the prevalence of substance use in primary care settings. Objectives: To compare the prevalence and characteristics of patients at risk for substance use disorders in Tijuana and East Los Angeles (LA) community clinics with special attention paid to drug use. Methods: This was an observational, cross-sectional, analytical study, comparing substance use screening results from patients in Tijuana and LA. The settings were 2 community clinics in LA and 6 in Tijuana. Participants were 2, 507 adult patients in LA and 2, 890 in Tijuana eligible for WHO Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) screening during March–October 2013. Patients anonymously self-administered the WHO ASSIST on a tablet PC in the clinic waiting rooms. Results: Of eligible patients, 96.4% completed the ASSIST in Tijuana and 88.7% in LA (mean 1.34 minutes and 4.20 minutes, respectively). The prevalence of patients with moderate-to-high substance use was higher in LA than Tijuana for each substance: drugs 19.4% vs. 5.7%, alcohol 15.2% vs. 6.5%, tobacco 20.4% vs. 16.2%. LA patients born in Mexico had 2x the odds and LA patients born in the United States had 6x the odds of being a moderate-to-high drug user compared to Tijuana patients born in Mexico. Conclusions: Moderate-to-high drug use is higher in LA than in Tijuana but rates are sufficiently high in both to suggest that screening for drug use (along with alcohol and tobacco use) should be integrated into routine primary care of community clinics in both cities.